2008
DOI: 10.1246/bcsj.81.1554
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Self-Assembly into One-Dimensional Nanotube Architectures and Exploitation of Their Functions

Abstract: This review article focuses on the self-assembly of amphiphilic molecules into discrete, hollow cylindrical tubular architectures (organic nanotubes). Research on nanotube formation from dumbbell-shaped peptide lipids, 1-O-glucopyranoside and 1-N-glucopyranosylamide lipids, and wedge-shaped bolaamphiphilic glycolipids with carboxylic, amino, or oligoglycine groups at one end has been outlined with their characteristic self-assembly. Finally, recent progress in mass production, dimension control, and novel func… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
26
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 58 publications
(26 citation statements)
references
References 104 publications
0
26
0
Order By: Relevance
“…However, applications for these organic nanotubes have not been studied because the efficient mass production of these molecules has never been achieved. Interestingly, after the self-assembly of newly designed molecules in alcoholic solvents, such as ethanol, we found that evaporation of the solvent left tubular material in quantities more than 1000-fold greater than those when using the same volume of water (Shimizu, 2008b;Asakawa et al, 2009). Thus, 100 g of organic nanotubes can be readily produced in a laboratory and 10 kg in a factory.…”
Section: Introductionmentioning
confidence: 97%
“…However, applications for these organic nanotubes have not been studied because the efficient mass production of these molecules has never been achieved. Interestingly, after the self-assembly of newly designed molecules in alcoholic solvents, such as ethanol, we found that evaporation of the solvent left tubular material in quantities more than 1000-fold greater than those when using the same volume of water (Shimizu, 2008b;Asakawa et al, 2009). Thus, 100 g of organic nanotubes can be readily produced in a laboratory and 10 kg in a factory.…”
Section: Introductionmentioning
confidence: 97%
“…In particular, the use of sugars is of specific interest because of their biologically-relevant functionality 40,41 occurring in cell-cell agglutination mechanisms, but new nanotechbased applications are also being explored. 42,24 Among this class of compounds, sophorolipids, natural bolaform glycolipids, can be obtained from the fermentation process of the yeast Starmerella bombicola (Figure 1a) and are the best bioderived candidates to substitute their synthetic counterparts previously studied, 43,44 both in terms of properties and conditions of productions. 45,46 Even if predictions cannot be done, it has been empirically observed that fibers with nanoscale chirality can be formed in glycolipid-based systems if specific sugar-to-lipid linkers like phenyl, 15 phenylamide 47 or amidopyridine 48 groups are used over simple ether bonding.…”
Section: Introductionmentioning
confidence: 99%
“…phospholipids, cholesterol) are used, and glucosomesa re only composed of b-d-glucose b(1,2) (sophorose)containing lipids;2)the compositions of the externaland internal membrane vesicles is expected to be the same;3 )wep roduce av esicle-in-vesicle system by using as imple pH-change approachi nstead of any of the known complex methods described in the literature. The glycolipidss hown here certainly contributet oe nlarging the wide complexity of glycolipid selfassembly behaviori nw ater; [27][28][29][30][31][32] in addition, given the importance of carbohydrates in glycobiology and medicine, [33] this new class of stimuli-responsive multicompartment glycosylated vesicles could pave the way to the development of complex delivery systems.…”
Section: Introductionmentioning
confidence: 99%